Penerapan Modul Discovery Learning Berbantuan Quick Response Code (QR Code) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMPN 4 Sungguminasa - Nur Fadilah. S; Sitti Rahma Yunus; Nurhayani H. Muhiddin (Celebes Science Education, 2026)
This study aims to determine: (1) The level of learning outcomes of class VIII students of SMPN 4 Sungguminasa before and after the implementation of the QR Code-assisted discovery learning module (2) Improvement in learning outcomes of class VIII students after the implementation of the QR Code-assisted discovery learning module (3) The implementation of the QR Code-assisted discovery learning module can significantly improve learning outcomes in class VIII students (4) Significant similarities in improving learning outcomes of class VIII students taught with the implementation of the QR Code-assisted discovery learning module. This type of research is pre-experimental research and the research design is One Group Pretest-Posttest Design. The sample was selected using the Purposive Sampling technique and obtained 56 students from 2 classes, namely class VIII A 26 people and VIII G 30 people. The instruments in this study were multiple choice questions. The data analysis technique was descriptive and inferential. The results of the analysis concluded: (1) The category of learning outcomes of class VIII students in the pretest obtained an average score of 10.69 in the medium category and the posttest obtained an average score of 18.42 in the high category. (2) The increase in learning outcomes of class VIII students after the implementation of the QR Code-assisted discovery learning module is in the medium category with an N-Gain of 0.54. (3) The implementation of the QR Code-assisted discovery learning module can significantly improve learning outcomes in class VIII students (4) There is a significant similarity in the improvement in learning outcomes of class VIII students taught with the implementation of the QR Code-assisted discovery learning module.